General Principles and Challenges of Public Administration Organization in the Slovak Republic - Jakab, Radomír (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
The organization of public administration in the Slovak Republic has undergone significant changes over the last 30 years. Following the fall of the communist regime, it became necessary to adjust public administration in accordance with democratic principles and the rule of law. Various nonlegal aspects, especially social, geographical, historical, and economic determinants, have also affected its formation. The chapter therefore examines each of those influences that have both shaped and continue to shape the current form of public administration organization. Public administration is part of the exercise of state power, the limits of which are set by the Constitution. Therefore, it is necessary to examine the implications of constitutional law and its principles for public administration. Public administration depends on the political management of the state by the legislative and executive branches of state power. Simultaneously, it was controlled by the judiciary. Therefore, it is also necessary to reflect on the relationships between the bodies representing these branches of power and public administration. Public administration is conducted by several entities with different roles and responsibilities. Therefore, we focused on examining these entities. The primary focus is on public administration bodies, that is, the bodies of the state and entities derived from the state. In this context, we refer to the principles of their construction and integration into the organization of public administration. Finally, the current challenges facing the organization of public administration in the Slovak Republic are formulated, and certain trajectories of its development are outlined.KEYWORDS public administration, public administration bodies, constitutional principles, principles of public administration construction, self-government  Bibliography Bröstl, A., Holländer, P., Príbelský, P. (2021) Ústavné právo Slovenskej republiky. Plzeň: Vydavatelství a nakladatelství Aleš Čeněk.Cepek, B. (2018) Správne právo hmotné. Všeobecná časť. Bratislava: Wolters Kluwer.Fiala, Z. (2015) Evropská veřejná správa. Praha: Univerzita Jana Amose Komenského.Gašpar, M. (1973) Československé správne parvo. Bratislava: Obzor.Gašpar, M. (1990) Československé správne právo hmotné. Bratislava: Právnická fakulta Univerzity Komenského v Bratislave.Giba, M. (2019) Ústavné právo. Bratislava: Wolters Kluwer.Handrlica, J. (2017) Transteritoriální správní akty: studie z mezinárodního správního práva. Praha: Národohospodářský ústav Josefa Hlávky.Hašanová, J. (2011) Správne právo. Všeobecná a osobitná časť. Bratislava: VEDA.Hendrych, D. (2003) Správní věda: teorie veřejné správy. Praha: ASPI.Hendrych, D. (2016) Správní právo: obecná část. V Praze: C.H. Beck.Hrtánek, L. (2013) Model optimálneho fungovania modernej štátnej správy. Bratislava: EUROKÓDEX.Jakab, R., Molitoris, P. (2018) Správne právo procesné. Košice: ŠafárikPress.Jakab, R. (2020a) ‘Administratívnoprávna zodpovednosť in Jakab, R. (ed.) Správne právo hmotné. Všeobecná čast. Košice: ŠafárikPress, pp. 187–213.Jakab, R. (2020b) ‘Správne právo’ in Jakab, R. (ed.) Správne právo hmotné. Všeobecná časť. Košice: ŠafárikPress, pp. 8–35.Jakab, R. (2020c) ‘Subjekty správneho práva’ in Jakab, R. (ed.) Správne právo hmotné. Všeobecná časť. Košice: ŠafárikPress, pp. 48–64.Jakab, R. (2020d) ‘The Influence of EU Law on public Administration in New Member S t a t e s ’, Public Governance, Administration and Finances Law Review: in the European Union and Central and Eastern Europe, 5(1), pp. 48–61 [Online]. Available at: https://doi.org/10.53116/pgaflr.2020.1.3 (Accessed: 15 February 2024).Jakab, R., Seman, T., Jančát, L. (2020) Transteritoriálne správne akty v podmienkach Európskej únie a Slovenskej republiky. Univerzita Pavla Jozefa Šafárika v Košiciach – Vydavateľstvo ŠafárikPress; https://doi.org/10.33542/TSA2020-919-1.Jesenko, M. (2010) ‘Ústavné východiská samosprávy obce a právo na samosprávu’ in Palúš, I., Jesenko, M., Krunková, A. (eds.) Obec ako základ územnej samosprávy. Košice: Univerzita Pavla Jozefa Šafárika v Košiciach, pp. 1–30.Kindl, M. (2009) Základy správního práva. Plzeň: Vydavatelství a nakladatelství Aleš Čeněk.Košičiarová, S. (2022) Správne právo hmotné: všeobecná časť. Plzeň: Vydavatelství a nakladatelství Aleš Čeněk.Koudelka, Z. (2011) Prezident republiky. Praha: Leges.Lukeš, Z. (1981) Československé správní právo – obecná část. Praha: Panorama.Machajová, J. (2009) Všeobecné správne právo. Bratislava: Eurokódex.Machajová, J. (2014) Všeobecné správne právo. Bratislava: Eurokódex.Martvoň, A. (2017) ‘Aktuálne teoreticko-právne problémy týkajúce sa zmeny (resp. presunu) kompetencií orgánov štátnej správy’ in Ivora, J. (ed.) Paneurópske právnické forúm. II. ročník. Zborník príspevkov z vedeckej konferencie doktorandov a mladých vedeckých pracovníkov. Bratislava: Paneurópska vysoká školy, pp. 237–244.Orosz, L., Šimuničová, K. (1998) Prezident v ústavnom systéme Slovenskej republiky. Bratislava: Veda.Palúš, I., Somorová, Ľ. (2004) Štátne právo Slovenskej republiky. Košice: Univerzita Pavla Jozefa Šafárika v Košiciach.Palúš, I., Jesenko, M., Krunková, A. (2010) Obec ako základ územnej samosprávy. Košice: Univerzita Pavla Jozefa Šafárika v Košiciach.Pomahač, R., Handrlica, J. (2012) Evropské správní právo. V Praze: C.H. Beck.Posluch, M., Cibulka, Ľ. (2003) Štátne právo Slovenskej republiky. Šamorín: Heureka.Průcha, P. (2004) Správní právo: obecná část. Brno: Masarykova univerzita.Seman, T. (2020) ‘Verejná správa‘ in Seman, T., Jakab, R., Tekeli, J. (eds.) Správne právo hmotné. Všeobecná časť. Košice: ŠafárikPress, pp. 36–47.Škultéty, P., Raučinová, P., Tóth, J. (2009) Správne právo hmotné: Všeobecná časť. Šamorín: Heureka.Škultéty, P., Andorová, P., Tóth, J. (2012) Správne právo hmotné. Všeobecná časť. Bratislava: Heureka.Seman, T., Jakab, R., Tekeli, J. (2020) Správne právo hmotné. Všeobecná časť. Košice: ŠafárikPressSládeček, V. (2009) Obecné správní právo. Praha: ASPI.Sládeček, V. (2019) Obecné správní právo. Praha: Wolters Kluwer.Statistical Office of the Slovak Republic [Online]. Available at: http://statdat.statistics.sk/cognosext/cgi-bin/cognos.cgi?b_action=cognosViewer&ui.action=run&ui.object=storeID%28%22i0C852CAA5451437C92774DB33EC08675%22%29&ui.name=Ve%C4%BEkostn%C3%A9%20skupiny%20obc%C3%AD%20-%20SR%2C%20oblasti%2C%20kraje%2C%20okresy%2C%20mesto%2C%20vidiek%20%5Bom7023rr%5D&run.outputFormat=&run.prompt=true&cv.header=false&ui.backURL=%2Fcognosext%2Fcps4%2Fportlets%2Fcommon%2Fclose.html&run.outputLocale=en (Accessed: 6 March 2023).Tekeli, J., Hoffmann, M. (2013) Kontrola v obecnej samospráve. Bratislava: EUROKÓDEX.Tekeli, J. (2020a) ‘Organizácia verejnej správy’ in Seman, T., Jakab, R., Tekeli, J. (eds.)Správne právo hmotné. Všeobecná časť. Košice: ŠafárikPress, pp. 65–129.Tekeli, J. (2020b) ‘Záruky zákonnosti vo verejnej správe’ in Seman, T., Jakab, R., Tekeli, J. (eds.) Správne právo hmotné. Všeobecná časť. Košice: ŠafárikPress, pp. 172–186.Tekeli, J., Hoffmann, M., Tomáš, L. (2021a) Zákon o obecnom zriadení. Bartislava: Wolters Kluwer.Tekeli, J., Tomáš, L., Hoffmann, M. (2021b) Zákon o samosprávnych krajoch: komentár. Praha: Wolters Kluwer.Vrabko, M. (2012) Správne právo hmotné: Všeobecná časť. Bratislava: C.H. Beck.Vrabko, M. (2018) Správne právo hmotné: Všeobecná časť. Bratislava: C. H. Beck SK.